2019
DOI: 10.1016/j.cell.2019.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-Refeeding Impacts Immune Cell Dynamics and Mucosal Immune Responses

Abstract: Nutritional status potentially influences immune responses; however, how nutritional signals regulate cellular dynamics and functionality remains obscure. Herein, we report that temporary fasting drastically reduces the number of lymphocytes by $50% in Peyer's patches (PPs), the inductive site of the gut immune response. Subsequent refeeding seemingly restored the number of lymphocytes, but whose cellular composition was conspicuously altered. A large portion of germinal center and IgA + B cells were lost via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 76 publications
5
118
2
Order By: Relevance
“…While our study was not purposed to decipher the molecular communication between organs or to investigate the migratory behaviors or composition of immune cells under fasting conditions [4][5][6], our study highlights the centrality of immune-transcriptomic modulations during STF. Using a combinatorial data analysis approach, we provide evidence for the existence of an organ network, formed by the similarities of their biological processes, and the prominent role of the immune system in sensing and modulating systemic homeostatic perturbations in the absence of infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our study was not purposed to decipher the molecular communication between organs or to investigate the migratory behaviors or composition of immune cells under fasting conditions [4][5][6], our study highlights the centrality of immune-transcriptomic modulations during STF. Using a combinatorial data analysis approach, we provide evidence for the existence of an organ network, formed by the similarities of their biological processes, and the prominent role of the immune system in sensing and modulating systemic homeostatic perturbations in the absence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying fasting-induced effects on the immune system remain largely unknown and only recently started to be elucidated [83]. Three recent studies demonstrated that monocytes, naïve B cells, and memory CD8 T cells use bone marrow as a refuge during periods of energy reduction to maintain systemic immune-responsiveness [4][5][6]. These studies also provided new insights into the integrated immunometabolic response in a state of energy deprivation.…”
Section: The Immune System In the Context Of Short-term Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Upon re-introduction of calories, naive B cells migrated back to Peyer's patches. 73 Therefore, it is possible that CR may modulate B cell populations and autoantibody levels in lupus. Within the innate immune system, circulating monocyte frequency and functionality were reduced in response to fasting in both humans and mice, which improved clinical parameters in EAE.…”
Section: Lupus and Sys Temi C Me Tabolis Mmentioning
confidence: 99%
“…tion and HSPC homing are reportedly important to maintain the immune response and hematopoiesis, respectively 38,39 . To assess a potential role for NE in blood cell migration into the BM, we first performed TCA of NE and 10 minutes later injected mice i.v.…”
Section: Transendothelial Migration Of Lymphocytes Into Decreases Aftmentioning
confidence: 99%